Impact of an additional chronic BDNF reduction on learning performance in an Alzheimer mouse model - Psotta, Laura; Rockahr, Carolin; Gruss, Michael; Kirches, Elmar; Braun, Katharina; Lessmann, Volkmar; Bock, Jörg; Endres, Thomas (Frontiers in Behavioral Neuroscience, 2015)
There is increasing evidence that brain-derived neurotrophic factor (BDNF) plays a crucial role in AD pathology. A number of studies demonstrated that AD patients exhibit reduced BDNF levels in the brain and the blood serum, and in addition, several animal-based studies indicated a potential protective effect of BDNF against Aβ-induced neurotoxicity. In order to further investigate the role of BDNF in the etiology of AD, we created a novel mouse model by crossing a well-established AD mouse model (APP/PS1) with a mouse exhibiting a chronic BDNF deficiency (BDNF+/-). This new triple transgenic mouse model enabled us to further analyze the role of BDNF in AD in vivo. We reasoned that in case BDNF has a protective effect against AD pathology, an AD-like phenotype in our new mouse model should occur earlier and/or in more severity than in the APP/PS1-mice. Indeed, the behavioral analysis re-vealed that the APP/PS1-BDNF+/–mice show an earlier onset of learning impairments in a two-way active avoidance task in comparison to APP/PS1- and BDNF+/–mice. However in the Morris water maze test, we could not observe an overall aggrevated impairment in spatial learning and also short-term memory in an object recognition task remained intact in all tested mouse lines. In addition to the behavioral experiments, we analyzed the amyloid plaque pa-thology in the APP/PS1 and APP/PS1-BDNF+/–mice and observed a comparable plaque den-sity in the two genotypes. Moreover, our results revealed a higher plaque density in prefrontal cortical compared to hippocampal brain regions. Our data reveal that higher cognitive tasks requiring the recruitment of cortical networks appear to be more severely affected in our new mouse model than learning tasks requiring mainly sub-cortical networks. Furthermore, our observations of an accelerated impairment in active avoidance learning in APP/PS1-BDNF+/–mice further supports the hypothesis that BDNF deficiency amplifies AD-related cognitive dysfunctions.